Perception of Millennial Generation about Global Issue of Citizenship in College Student Community of Democratia Sebelasmaret University - Guntoro, Muhammad Yogi; Gunawati, Dewi; Rusnaini, Rusnaini (Budapest International Research and Critics University, 2020)
Citizenship status also refers to the competence or capacity of a person to participate in building and contributing to society. The citizenship competencies are knowledge, attitudes, and skills of a person in participating and responsible in the life of the community and state at the local, national, and international levels. The citizens must take responbility to make a better world in this era much issue in global space in civic discussions room student give the literacy about global issue of citizenship to build a perception in citizens. This research is a qualitative study carried out in the collage student community of democratia Sebelas Maret University. MillennialÂ are invited to study various issues regarding climate change and they study these problems using ecological citizenship as their scientific basis, namely through ecological citizenship as a means of changing thinking about the urgency of the importance of handling climate change from the perspective of citizens. With increasing literacy on global justice, students will understand the importance of their role as part of global society in helping to realize the importance of mutual peace that global justice is a shared responsibility.